Post‐traumatic stress disorder symptoms in pregnant Australian Indigenous women residing in rural and remote New South Wales: A cross‐sectional descriptive study. (7th April 2017) - Mah, Beth; Weatherall, Loretta; Burrows, Julie; Blackwell, Caroline C.; Gwynn, Josephine; Wadhwa, Pathik; Lumbers, Eugenie R.; Smith, Roger; Rae, Kym M.
Abstract : Background: Pregnancy can be a stressful time for many women. There is ample evidence of numerous physical and mental health inequities for Indigenous Australians. For those Indigenous women who are pregnant, it is established that there is a higher incidence of poor physical perinatal outcomes when compared with non‐Indigenous Australians. However, little evidence exists that examines stressful events and post‐traumatic stress disorder (PTSD) symptoms in pregnant women who are members of this community. Aims: To quantify the rates of stressful events and PTSD symptoms in pregnant Indigenous women. Methods: One hundred and fifty rural and remote Indigenous women were invited to complete a survey during each trimester of their pregnancy. The survey measures were the stressful life events and the Impact of Events Scale. Results: Extremely high rates of PTSD symptoms were reported by participants. Approximately 40% of this group exhibited PTSD symptoms during their pregnancy with mean score 33.38 (SD = 14.37) significantly higher than a study of European victims of crisis, including terrorism attacks (20.6, SD = 18.5). Conclusions: The extreme levels of PTSD symptoms found in the women participating in this study are likely to result in negative implications for both mother and infant. An urgent response must be mounted at government, health, community development and research levels to address these findings. Immediate attention needs to focus on the development of interventions to address the high levels of PTSD symptoms that pregnant Australian Indigenous women experience.